Familial Relationship Outcomes of Coming Out as an Atheist. (15th May 2015) - Zimmerman, Kevin J.; Smith, Jesse M.; Simonson, Kevin; Myers, Benjamin W.
How do families react when a member "comes out" as an atheist? As one of America's most stigmatized groups, atheists often find members of their own families reacting with anger and rejection, an inability to communicate effectively, and distrust. Many atheists, however, feel continued support and acceptance from family members, experience greater authenticity in their communication, and enjoy relationships with family members who manage to adapt to the atheist's disclosure of nonbelief. This qualitative study reports the experiences of 80 atheists when they tell family members that they do not believe in God. Participant comments were coded as either unsupportive or supportive of the relationship, and lend support to the Circumplex Model of family functioning.